Graphitic carbon nitride-based concoction for detection of melamine and R6G using surface-enhanced Raman scattering. (September 2022) - Tiwari, Mohit; Singh, Aditya; Thakur, Deepak; Pattanayek, Sudip K.
Abstract: Melamine adulteration in dairy-based products harms the ecosystem and human health. The current study examined the impact of gold nanoparticles (AuNPs) onto g-C3 N4 /Ni3 N (Au/g-C3 N4 /Ni3 N) nanocomposite material for the SERS-based melamine detection. The intended nanocomposites were synthesized using a simple and cost-effective fabrication process. Designing the surface and bandgap of graphitic carbon nitride (g-C3 N4 ) are critical for improving surface-enhanced Raman scattering (SERS) performance by suppressing the recombination rate of the photogenerated electron-hole pairs leading to an effective charge transfer mechanism. The developed SERS-based nanocomposite material is capable of detecting R6G with an enhancement factor of 1.82 × 10 8, whereas, in the case of Melamine, the average enhancement factor is evaluated to be 2.56 × 10 7 . Besides, the SERS substrate has good stability and Raman signal sensitivity; the Raman intensity of the Au@CNN substrate shows low RSD values for Melamine and R6G. We have used the finite-difference time-domain (FDTD) technique to theoretically study the contribution of the electromagnetic field enhancement in Au@g-C3 N4 /Ni3 N. The obtained result confirms that the electromagnetic field enhancement contributes significantly to the entire enhancement of the SERS substrate. In addition, the adsorption is analyzed using the surface area, size of the molecule, and various adsorption models. The best fit is obtained using the Langmuir isotherm model due to the very low concentration of solutes. Graphical abstract: The effective charge transfer enabled the detection of Melamine through Surface-Enhanced Raman Scattering (SERS) using an Au/g-C3 N4 /Ni3 N composite. Image 1 Highlights: AuNPs modified g-C3 N4 /Ni3 N composite as a SERS substrate for melamine detection. The electromagnetic field enhancement in Au@g-C3 N4 /Ni3 N is confirmed from the FDTD simulation. NH4 F and Urea are utilized as the structural mediating agent to boost crystallinity in synthesizing g-C3 N4 /Ni3 N composite. The AuNPs were synthesized in situ photoreduction of Au 3+ . Theoretical correlations were utilized to analyze the interactions and define the sensing approach.